Ex-ante margin squeeze tests in the telecommunications industry: What is a reasonably efficient operator? (Revised: September 6, 2012) - Germain Gaudin; Claudia Saavedra Valenzuela (International Telecommunications Society (ITS), 2012)
In this paper, we study the adjustments made by National Regulatory Authorities to simple margin squeeze tests, in order to model a reasonably efficient operator. More precisely, by inspecting the possible differences between an entrant and an incumbent that would cause a market disadvantage for the former, we provide a formal economic framework that translates these ex-ante disadvantages into practical test adjustments. We identify five possible adjustments relevant to ex-ante margin squeeze tests, on the cost, the access charge, or the price parameters. We then review the implementation of margin squeeze tests by European telecommunications National Regulatory Authorities according to these adjustments, as to build a comparable benchmark of implementation choices.
Additional information: Revised Version: September 6, 2012; Is replaced by the following version: http://hdl.handle.net/10419/67955
Keywords: L51; L96; 330; Margin squeeze; Imputation test; Access regulation; Telecommunications